Oxford case histories in TIA and stroke - Pendlebury, Sarah T. (Oxford case histories, 2012)
"Based around the core curriculum for specialist trainees,Oxford Case Histories in Stroke features 51 well-structured, peer-reviewed cases from the Oxford Hospitals giving detailed coverage of the specialty, including diagnostic and management dilemmas. Each case comprises a brief clinical history and the relevant examination findings; details of investigations undertaken, followed by questions on differential diagnosis and management; and detailed answers and discussion. The question-and-answer format is designed to enhance the reader's diagnostic ability and clinical understanding. As part of the Oxford Case Histories series, this book is aimed at post-membership trainees and consultants and will be a useful resource for those preparing for exit examinations or revalidation. It will also be of interest to those who wish to improve their skills in diagnosis and management of a broad range of stroke disorders." -- Publisher's website.